Which novel teaching strategy is most recommended in medical education? A systematic review and network meta-analysis - Zhang, Shuai-Long; Ren, Si-Jing; Zhu, Dong-Mei; Liu, Tian-Yao; Wang, Lian; Zhao, Jing-Hui; Fan, Xiao-Tang; Gong, Hong (BMC medical education, 2024)
Aim There is no conclusive evidence which one is the optimal methodology for enhancing the quality and efficacy of learning for medical students. Therefore, this systematic review and network meta-analysis aims to evaluate and prioritize various teaching strategies in medical education, including simulation-based learning (SBL), flipped classrooms (FC), problem-based learning (PBL), team-based learning (TBL), case-based learning (CBL), and bridge-in, objective, pre-assessment, participatory learning, post-assessment, and summary (BOPPPS). Methods We conducted a comprehensive systematic search of PubMed, Embase, Web of Science, the Cochrane Library, and some key medical education journals up to November 31, 2023. The following keywords were searched in MeSH: (“medical students”) AND (“problem-based learning” OR “problem solving”) AND (“Randomized Controlled Trials as Topic”). Two authors independently carried out data extraction and quality assessment from the final selection of records following a full-text assessment based on strict eligibility criteria. Pairwise and network meta-analyses were then applied to calculate pooled standardized mean differences (SMDs) and 95% confidence intervals (95%CIs) using a random-effects model. Statistical analysis was performed by R software (4.3.1) and Stata 14 software. Results A total of 80 randomized controlled trials with 6,180 students were included in the study. Compared to LBL, CBL (SMD = 1.19; 95% CI 0.49–1.90; p < 0.05; SUCRA = 89.4%), PBL (SMD = 3.37; 95% CI 1.23–5.51; p < 0.05; SUCRA = 93.3%), and SBL (SMD = 2.64; 95% CI 1.28–4.00; p < 0.05; SUCRA = 96.2%) were identified as the most effective methods in enhancing theoretical test scores, experimental or practical test scores, and students’ satisfaction scores, respectively. Furthermore, subgroup analysis indicated that CBL (SUCRA = 97.7%) and PBL (SUCRA = 60.3%) were the most effective method for enhancing learning effectiveness within clinical curricula. Conclusions Among the six novel teaching strategies evaluated, CBL and PBL are more effective in enhancing the quality and efficacy of learning for medical students; SBL was determined to offer a superior learning experience throughout the educational process. However, this analysis revealed only minor differences among those novel teaching strategies.